MaTrEx AM: A new hybrid additive manufacturing process to selectively control mechanical properties - Moetazedian, Amirpasha; Allum, James; Gleadall, Andrew; Mele, Elisa; Silberschmidt, Vadim V. (Additive Manufacturing, 2021)
This study is the first to demonstrate how mechanical and geometrical properties of polylactide (PLA) and acrylonitrile butadiene styrene (ABS) additively manufactured with material extrusion can be selectively tailored using a newly devised treatment method of chemical immersion in acetone. This combination of manufacturing and chemical treatment results in a hybrid process capable of modifying mechanical behaviour in a predictable and time-controlled manner. Key new understanding is generated by analysing short-term effects (tested immediately after immersion) on mechanical and geometrical properties of printed specimens, with different immersion times (1–60 seconds) causing significant increases in strain-at-fracture - up to 25- and 16-fold for PLA and ABS, respectively. In the long-term mechanical properties were found to recover by up to 90% of those for untreated specimens in ABS within 3 hours, while PLA properties recovered after 60 days. Importantly, while mechanical properties in both PLA and ABS recovered, the geometrical changes were retained. Annealing allowed the recovery time to be shortened: PLA specimens achieved full recovery within 24 hours. Chemical immersion provides significant advantages over widely used vapour-based treatment methods, since it allows selective application to achieve and localised changes of mechanical and geometrical properties. Applications of this new hybrid process, called Material Treatment Extrusion Additive Manufacturing (MaTrEx AM), are presented, including the capability to add new functionality (dramatically increased plasticity) to material structures manufactured with PLA and ABS. The implementation of MaTrEx AM as a hybrid manufacturing system is demonstrated. MatrEX AM enabled selective and localised modification of mechanical properties to increase toughness and redirect strain into selected regions of a mesh material.
Keywords: Manufacturing engineering; Hybrid manufacturing; Mechanical properties; Mechanical recovery; Chemical treatment; Additive manufacturing